Red herring : a Joe Gunther novel - Mayor, Archer (New York : Minotaur Books, 2010)
"Joe Gunther and his team at the VBI (Vermont Bureau of Investigation) are faced with the most complex and deadly case of their careers when they are called in to investigate a series of violent deaths that appear unrrelated to one another. That is, until telltale clues reveal a linkage between the deaths. Even more chilling, the crime scenes were staged and, despite initial appearances, those deaths are, in fact, murders. And that clue--a single drop of unexplained blood at each crime scene, coming from three additional unknown people--leaves the police with more questions than answers" --Cover, p. 2.
Keywords: Gunther, Joe (Fictitious character) -- Fiction; Police -- Vermont -- Fiction; Serial murders -- Fiction; Serial murder investigation -- Fiction; Vermont -- Fiction; Mystery fiction